2023
DOI: 10.3390/jcs7070266
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Mechanical Property Evaluation and Morphology Study of Moisture-Treated Hemp–Banana Natural-Fiber-Reinforced Green Composites

Ravi Yerraiahgarahalli Venkataravanappa,
Avinash Lakshmikanthan,
Natesan Kapilan
et al.

Abstract: The development of many engineered product applications for automobiles and aircraft parts has initiated the search for novel materials as alternatives to metal matrix composites (MMCs). Natural-fiber-reinforced polymer composites offer distinct advantages such as biodegradability, eco-friendliness, flexibility, low density, and higher specific strengths, etc. This study focuses on natural-fiber (hemp and banana)-fabric-reinforced polymer composites suitable for exterior-engineered parts. The hand lay-up proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…SPSS (IBM SPSS Statistics 26) was used for statistical analysis. ANOVA was applied for the test of significant differences in data, and statistical significance was determined as statistically (* p < 0.05) and highly (** p < 0.01) significant, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…SPSS (IBM SPSS Statistics 26) was used for statistical analysis. ANOVA was applied for the test of significant differences in data, and statistical significance was determined as statistically (* p < 0.05) and highly (** p < 0.01) significant, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, fiber swelling caused by moisture leads to significant changes in the dimensional stability of the composite, inducing cracking in the matrix and damage to the fiber/matrix interface, thereby increasing the energy dissipation of the composites [ 8 ]. In contrast, Venkataravanappa et al reported negligible alterations in dimensional stability after water absorption in hybrid specimens of hemp and banana fibers combined with polyester resin [ 11 ]. Their study revealed minimal variation in hybrid composites, whereas significant effects were observed in specimens containing hemp or banana fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, optimized processes that minimize the negative impact on the environment are becoming increasingly important in modern manufacturing [23]. Trends include, among others, the search for new materials, such as ecological composites [24]. The authors of [25] describes a case study that allows for the evaluation of a manufacturing process in terms of environmental friendliness.…”
Section: Introductionmentioning
confidence: 99%